The Effect Of Capital Structure On Company Value With Profitability As An Intervening Variable - Risna Kamisanti; Anwar Ramli; Nurul Fadilah Aswar (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
Indonesia’s palm oil plantation subsector plays a strategic role in supporting national economic growth, export performance, and foreign exchange earnings. However, during the 2020–2024 period, this sector faced significant challenges, including the COVID-19 pandemic, volatility in crude palm oil (CPO) prices, export restriction policies, rising production costs, and sustainability regulations imposed by the European Union. These conditions created uncertainty regarding firms’ financing decisions, profitability, and market valuation. This study aims to examine the effect of capital structure on firm value, both directly and indirectly through profitability as an intervening variable, in palm oil plantation companies listed on the Indonesia Stock Exchange (IDX). This research employs a quantitative explanatory approach with a causal-associative design using panel data. The sample consists of 13 palm oil plantation companies selected through purposive sampling based on data availability during the 2020–2024 period. Capital structure is measured using the Debt-to-Equity Ratio (DER) and Debt-to-Asset Ratio (DAR), profitability is proxied by Return on Assets (ROA) and Return on Equity (ROE), and firm value is measured using Price-to-Book Value (PBV) and Tobin’s Q. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM), which is suitable for small samples and complex mediation models. The results indicate that capital structure has a moderate positive effect on profitability but a weak and negative effect on firm value. Profitability does not significantly influence firm value and does not mediate the relationship between capital structure and firm value. These findings suggest that higher leverage does not necessarily enhance firm value in the Indonesian palm oil sector during periods of economic uncertainty. This study contributes to the post-pandemic empirical literature and provides insights for managers and investors in optimizing financial policies under volatile market conditions.